[tex]a=6\cdot10^7\\b=2,5\cdot10^6\\\\a+b=6\cdot10^7+2,5\cdot10^6=60\cdot10^6+2,5\cdot10^6=62,5\cdot10^6=6,25\cdot10^7\\a-b=6\cdot10^7-2,5\cdot10^6=60\cdot10^6-2,5\cdot10^6=57,5\cdot10^6=5,75\cdot10^7[/tex]
[tex]a=5,2\cdot10^{-4}\\b=3,7\cdot10^{-5}\\\\a+b=5,2\cdot10^{-4}+3,7\cdot10^{-5}=52\cdot10^{-5}+3,7\cdot10^{-5}=55,7\cdot10^{-5}=5,57\cdot10^{-5}\\a-b=5,2\cdot10^{-4}-3,7\cdot10^{-5}=52\cdot10^{-5}-3,7\cdot10^{-5}=48,3\cdot10^{-5}=4,83\cdot10^{-5}[/tex]
[tex]a=1,2\cdot10^{13}\\b=9,8\cdot10^{12}\\\\a+b=1,2\cdot10^{13}+9,8\cdot10^{12}=12\cdot10^{12}+9,8\cdot10^{12}=21,8\cdot10^{12}=2,18\cdot10^{13}\\a-b=1,2\cdot10^{13}-9,8\cdot10^{12}=12\cdot10^{12}-9,8\cdot10^{12}=2,2\cdot10^{12}[/tex]